Penerapan Metode Inhalasi Jahe untuk Menurunkan Mual Muntah pada Pasien Post SC - Galih Pria Pambayun; Bayu Despriyanto Pratama (Solusi Bersama : Jurnal Pengabdian dan Kesejahteraan Masyarakat, 2024)
Post-Caesarean Section (CS) nausea and vomiting are common complications arising from the effects of anesthesia and hormonal changes, which can significantly affect patient comfort and hinder recovery. The administration of antiemetic drugs, while effective, often results in side effects, necessitating the need for alternative non-pharmacological treatments that are both safe and effective. This study aims to assess the effectiveness of ginger inhalation therapy in reducing nausea and vomiting in post-CS patients at PKU Muhammadiyah Surakarta Hospital. A participatory approach was used involving 15 patients, who were divided into two groups: an experimental group receiving ginger inhalation therapy and a control group. Nausea levels were measured using the Numeric Rating Scale (NRS) both before and after the intervention. The results indicated that the group receiving ginger inhalation therapy experienced a significant reduction in nausea, with the average NRS score decreasing from 7.2 to 3.8. In contrast, the control group’s NRS score decreased from 7.2 to 6.5. These findings suggest that ginger inhalation therapy is an effective, easy-to-implement, and low-risk alternative to pharmacological treatments for managing postoperative nausea and vomiting. This method could serve as a valuable non-pharmacological option in the postoperative care of CS patients, offering a safe and accessible approach to improving patient outcomes.